Making the Inconspicuous, Manifest: Aesthetics of the Bedouins - Khan, Mamoona (Islamic Studies, 2015)
The research is aimed at exploring the aesthetics of a race that dwells in the region which is the cradle of Islam, habitants of which are generally labelled as uncouth and uncivilised. First half of this paper hence, strives to determine status of the race, probing the ethnicity of people that can rightly be entrusted the sobriquet, Bedouins. While the second half scrutinises about their sense of beauty and creativity by contemplating the annals of history, considering in mind that beauty and creativity are instinctive in man which is hard to be eluded. Religious chronicles and historical facts both are probed about contextually in this respect. Deciphering consequently that art is a human instinct, with which man cannot depart, although it is not one of his basic needs. But being instinctive its outlet emerges at once in propitious circumstances, and tries to peep out in the unpropitious.